2020
DOI: 10.2110/jsr.2020.45
|View full text |Cite
|
Sign up to set email alerts
|

A case for the growth of ancient ooids within the sediment pile

Abstract: In modern ooid-forming environments in the Caribbean, aerobic respiration of organic matter below the sediment–water interface drives an increase in pCO2 and a corresponding decrease in carbonate saturation state (Ω) that creates shallow sediment porewater that is neutral or slightly caustic to carbonate. The locus of ooid growth, therefore, is presumed to be in the water column during suspension, where supersaturation with respect to calcium carbonate is the norm. In the past, however, during conditions of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 78 publications
0
42
0
Order By: Relevance
“…While there is evidence for collisional abrasion, the predominance of frictional abrasion suggests that the primary mode of transport occurs between the threshold for motion and the threshold for saltation (Novák-Szabó et al, 2018). In many cases, the Δ sphericity is very close to that predicted by SNG, which could be the result of infrequent transport or growth in the sediment pile (sensu Anderson et al, 2020). Laboratory and natural experiments have shown that when the particle size is large, frictional abrasion dominates at low velocities, and at high velocities fragmentation occurs, instead of the chipping that occurs in smaller particles (see Figure 7 in Novák-Szabó et al ( 2018)).…”
Section: The Growth History Of Giant Ooidsmentioning
confidence: 87%
See 4 more Smart Citations
“…While there is evidence for collisional abrasion, the predominance of frictional abrasion suggests that the primary mode of transport occurs between the threshold for motion and the threshold for saltation (Novák-Szabó et al, 2018). In many cases, the Δ sphericity is very close to that predicted by SNG, which could be the result of infrequent transport or growth in the sediment pile (sensu Anderson et al, 2020). Laboratory and natural experiments have shown that when the particle size is large, frictional abrasion dominates at low velocities, and at high velocities fragmentation occurs, instead of the chipping that occurs in smaller particles (see Figure 7 in Novák-Szabó et al ( 2018)).…”
Section: The Growth History Of Giant Ooidsmentioning
confidence: 87%
“…Instead, the presence of fragments suggests that the ooids grew to their large size under calmer conditions (i.e., bed‐shear velocities below the threshold for saltation of the giant ooids), but were occasionally exposed to bed‐shear velocities high enough to cause fragmentation. Several scenarios exist that could explain both the size of the ooids and the occurrence of fragmentation including (1) the giant ooids grew in a calmer environment and were transported to a higher‐energy environment, (2) ooids grew within the sediment pile causing ooids to be oversized (Anderson et al., 2020), or (3) the ooids predominantly grew on the seafloor under calmer conditions where the dominant processes were surface normal growth and frictional abrasion from rolling, but occasional storms led to high bed‐shear velocities and fragmentation. Option one fails to explain why there are laminations on large, fragmented ooid cortices (Figure 9e).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations